Anemia That Presented with Desaturation: A Focus on Core Concepts - Lakshmi Shobhavat; Antonio D’Costa; Karthik Shroff (Case Reports in Pediatrics)
Background. Methemoglobinemia is a potentially life-threatening condition which presents with cyanosis and characteristic “chocolate-coloured blood.” Although a co-oximetry would give a prompt diagnosis, there have been multiple reports of misdiagnosing this treatable condition—from being diagnosed as sepsis to asthma and even being operated for “ruptured ectopic pregnancy.” Here, we report a case which presented without the classical signs of poisoning and methemoglobinemia—without vomiting, cyanosis, or chocolate-coloured blood. We also discuss the common misconceptions regarding anemia physiology and the pitfalls in diagnosing this condition and warn the reader regarding the reflexive use of antidotes like methylene blue. Case Presentation. A well-grown 3-year old boy presented with an acute history of irritability, cola-coloured urine, and desaturation on examination. The child was pale, with tachypnoea and in failure. Blood smear was suggestive of severe hemolytic anemia. Methemoglobinemia was diagnosed on co-oximetry. By focussing on physiologic principles of management rather than a specific antidote, the child was discharged home, well and active within 3 days of intensive care admission.